The relationship between Ambidextrous Leadership Behaviors and strategic supremacy Research analysis in the Ministry of Construction, Housing, Municipalities and Public Works (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of the research is to verify the relationship and influence between the ambidextrous leadership behaviors and the strategic supremacy in the Iraqi Ministry of Construction, Housing, Municipalities and Public Works, and to identify the reality of the behaviors and processes of the ambidextrous leadership prevailing among the administrative leaderships in the ministry in order to develop appropriate mechanisms and procedures that work to create a culture of ambidextrous leadership style Which enhances belonging and exclusivity among all employees and encourages creativity and innovation and directs them towards achieving strategic supremacy. Data were collected from an intentional sample of the administrative leaders working in the researched ministry and consisted of (89) respondents, and for the purpose of data analysis, and the statistical programs (SPSS, AMOS) were added by adopting statistical methods. The results showed the correctness of the correlation and influence relationships at the level of major variables and sub-dimensions, indicating the essential role of ambidextrous leadership to achieve the strategic supremacy in the Ministry of Construction, Housing, Municipalities and Public Works